Relationship between personal resources and indicators of biopsychological age in the Caucasus region of Russia - Zimina, Albina A; Zinatullina, Azaliya M; Fatianov, Georgiy V (Interacción y Perspectiva, 2022)
The paper reports on an experimental study of the relationship between biopsychological age and personal resources. The study uses the variables of biological, chronological, and psychological age, along with the relative biological aging index (BA-EBA), the relative psychological aging index (PA-CA), assessment of subjective psychological age, a life path questionnaire, and a resource questionnaire. Research results demonstrate that in young women aged 25-35, the resource of communication lowers the PA-CA index. A positive impact of sports on physiological health is found among women aged 36-55 despite the fact that they engage in it less as they get older. Women aged between 56 and 71 become less prone to risky behavior with age, which explains their higher psychological age. In the sample of 36-60-year-old men, it is notable that the resources of life organization, kindness, care, determination, vigor, and the need for achievement reduce the indicators of biological age. At the same time, sports exercise helps to lower the indicators of biological and psychological aging and contributes to anti-aging in men of this age group. Thus, the study shows that in each age period, women and men differ in their use of life resources, which affects the decrease or increase in biopsychological age.